2019
DOI: 10.1186/s13071-019-3539-z
|View full text |Cite
|
Sign up to set email alerts
|

rSjp40 inhibits activated hepatic stellate cells by promoting nuclear translocation of YB1 and inducing BMP-7/Smad1/5/8 pathway

Abstract: Background Activation of hepatic stellate cells is the dominant pathogenic event during the process of liver fibrosis. Bone morphogenic protein (BMP)-7 has recently been identified as an anti-fibrotic factor and leads to phosphorylation of Smad1/5/8 in activated hepatic stellate cells. Its expression can be upregulated by the transcriptional activator, Y-Box protein-1 (YB1). Previous studies have found that the recombinant Schistosoma japonicum protein p40 (rSjp40) can i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…It is indicated that the eggs were the main cause of pathological damage in the host after S. japonicum infection. Although there have been many studies on the mechanism of HSC in schistosomiasis liver brosis in recent years [29][30][31], most of them were performed in vitro with the Human HSCs line (LX2) since primary HSCs were di cult to isolate. Therefore, our team used S. japonicum-infected FVB/NJ mice to isolate primary HSCs for in vitro culture to investigate the mechanism of liver brosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is indicated that the eggs were the main cause of pathological damage in the host after S. japonicum infection. Although there have been many studies on the mechanism of HSC in schistosomiasis liver brosis in recent years [29][30][31], most of them were performed in vitro with the Human HSCs line (LX2) since primary HSCs were di cult to isolate. Therefore, our team used S. japonicum-infected FVB/NJ mice to isolate primary HSCs for in vitro culture to investigate the mechanism of liver brosis.…”
Section: Discussionmentioning
confidence: 99%
“…In murine studies, ribonuclease T2 stimulates a distinct Th2 immune response in the host by affecting the maturation of DCs, inducing the production of anti-inflammatory IL-10 by macrophages and the upregulation of IL-4 levels in the serum [ 40 ]. In contrast, S. japonicum -P40 inhibits fibrogenesis by reducing the activation of hepatic stellate cells and promoting apoptosis and senescence in these cells [ 33 , 34 , 35 ].…”
Section: Schistosome Egg Proteomics—technologies and Key Studiesmentioning
confidence: 99%
“…Similar to S. mansoni, S. japonicum eggs secrete several ribonucleases (T2, Oy and X25) that share sequence identity with omega-1 (31%, 52% and 35% respectively) and its own variant of P40 (66% sequence identity with Sm-P40). In murine models, ribonuclease T2 has been shown to stimulate a Th2 host immune response by affecting DC maturation, inducing macrophages to produce antiinflammatory IL-10 and upregulating serum levels of IL-4 [14], while Sj-P40 inhibits the progression of fibrosis by inhibiting HSC activation and promoting HSC apoptosis and senescence [15][16][17].…”
Section: Immunomodulation By the Schistosome Eggmentioning
confidence: 99%
“…Sm-P40 stimulation of murine lymphocytes induces interleukin (IL)-2 and interferon-gamma (IFN-γ) expression, both of which are considered Th1 cytokines, while Sj-P40 has been linked with decreasing hepatic stellate cell (HSC) activity and contribution to fibrosis by inducing apoptosis and senescence in these stellate cells [15][16][17][18]. Together, these proteins act to reduce local inflammation at the site of the granuloma and promote the regulated development of a fibrotic phenotype that assists egg survival and transmission.…”
Section: Introductionmentioning
confidence: 99%